1999
DOI: 10.1161/01.hyp.34.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine, Aortic Stiffness, and Renal Function in Hypertensive Patients

Abstract: Abstract-Hyperhomocysteinemia has been associated with both vascular structure alterations and vascular clinical end points. To assess the relation between plasma homocysteine, structure and function of large arteries, and the presence of clinical vascular disease, we investigated a population of 236 hypertensive patients. We estimated arterial stiffness by measuring the carotid-femoral pulse wave velocity. Total plasma homocysteine was determined by fluorometric high-performance liquid chromatography. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
83
1
10

Year Published

2002
2002
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 42 publications
7
83
1
10
Order By: Relevance
“…Recently, an inverse relation between a range of tHcy concentrations and endothelium-dependent coronary blood flow was documented [32]. Furthermore, it was shown that increased tHcy concentrations in patients with essential hypertension are strongly and independently correlated to stiffness of the aortic artery measured by aortic pulse wave velocity (adjusted for GFR) [33]. Thus, longstanding, mild to moderate hyperhomocysteinaemia could contribute to the development of hypertension through interference with the nitrovasodilator system and could therefore promote microvascular and macrovascular complications, which are mainly determined by hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an inverse relation between a range of tHcy concentrations and endothelium-dependent coronary blood flow was documented [32]. Furthermore, it was shown that increased tHcy concentrations in patients with essential hypertension are strongly and independently correlated to stiffness of the aortic artery measured by aortic pulse wave velocity (adjusted for GFR) [33]. Thus, longstanding, mild to moderate hyperhomocysteinaemia could contribute to the development of hypertension through interference with the nitrovasodilator system and could therefore promote microvascular and macrovascular complications, which are mainly determined by hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 The fact that other studies observed a significant association between tHcy levels and PWV is probably due to the fact that those studies were performed in subjects who were at a markedly increased risk of cardiovascular events. 11,27,28 Two other studies reported that acute rises in tHcy after oral methionine caused increased aortic stiffness. 29,30 We believe that this finding does not conflict with our results as these effects of tHcy were attained at concentrations that are not comparable to the epidemiological observations.…”
Section: Discussionmentioning
confidence: 99%
“…Since only nitric oxide-mediated vasodilation is damaged, the impact of Hcy on endothelium function may have small influence on blood pressure reduction response to benazepril. Finally, a high-plasma Hcy level might be associated with increased arterial stiffness as well as thickness (Bortolotto et al 1999;Malinow et al 1993;Nestel et al 2003; Smilde et al 1998), which may lead to a poor response to benazepril. But whether blood pressure can be directly affected by an increased arterial stiffness resulting from hyperhomocysteinemia remains to be elucidated (Davis et al 2001;Nestel et al 2003).…”
Section: Discussionmentioning
confidence: 99%